Did I Offend You or Did It? Agency Assignment in Interpersonal Apology. Issue 1 (2nd January 2020) - Wang, Yiwei; McGlone, Matthew S.
ABSTRACT: When apologizing to victims of transgressions, people may assign the agency for harm to themselves ("I'm sorry I offended you"), to the act ("I'm sorry it offended you"), or omit agency altogether ("I'm sorry you were offended"). They also may acknowledge or question the victim's harm by the choice of conjunction used to introduce an explanatory subordinate clause ("I'm sorry that you were offended" vs. "I'm sorry if you were offended"). Participants (n = 1, 118) were randomly assigned to read 1 of 12 versions of a scenario wherein someone commits a transgression (e.g., breaks a promise) and then apologizes. Versions varied on degree of offense (minor or major), apology agency assignment (transgressor, transgression, or omitted), and conjunction choice ("that" or "if"). Results indicated that apologies assigning agency to the transgressor or transgression invited more favorable perceptions of the transgressor than those omitting agency. However, there was no reliable main effect nor interaction involving subordinating conjunction choice. Our findings demonstrate the impact of strategic word choice in apology on victims' perceptions of transgressors.